2007
DOI: 10.1021/jm0612923
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Optimization of Non-Small Cell Lung Cancer Activity with Troxacitabine, l-1,3-Dioxolane-cytidine, Prodrugs

Abstract: l-1,3-Dioxolane-cytidine, a potent anticancer agent against leukemia, has limited efficacy against solid tumors, perhaps due to its hydrophilicity. Herein, a library of prodrugs were synthesized to optimize in vitro antitumor activity against non-small cell lung cancer. N4-Substituted fatty acid amide prodrugs of 10-16 carbon chain length demonstrated significantly improved antitumor activity over l-1,3-dioxolane-cytidine. These in vitro results suggest that the in vivo therapeutic efficacy of l-1,3-dioxolane-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…More importantly, since earlier studies identified that patients with low nucleoside transporter expressions, especially hENT1 and hCNT3, exhibit poor treatment and survival outcomes when treated with nucleoside analogs, we synthesized acyl prodrugs of DZNep to maximize its cytotoxic response. The results support increased lipophilicity as a means to bypass transport requirements and as a preferred strategy for enhancing nucleoside analog efficacy in pancreatic cancer cells [29], [30]. Second, unlike gemcitabine, DZNep is most likely not phosphorylated into an active form.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…More importantly, since earlier studies identified that patients with low nucleoside transporter expressions, especially hENT1 and hCNT3, exhibit poor treatment and survival outcomes when treated with nucleoside analogs, we synthesized acyl prodrugs of DZNep to maximize its cytotoxic response. The results support increased lipophilicity as a means to bypass transport requirements and as a preferred strategy for enhancing nucleoside analog efficacy in pancreatic cancer cells [29], [30]. Second, unlike gemcitabine, DZNep is most likely not phosphorylated into an active form.…”
Section: Discussionmentioning
confidence: 67%
“…3C). Since gemcitabine is well-known to rely heavily on nucleoside transporters for cellular activity, we examined the effects of an acyl derivative (C 24 H 41 N 3 O 5 ) of a less hydrophilic nucleoside analog, troxacitabine (log P of −0.66) [29], [30], in combination with DZNep Prodrug 1 on the same cell lines. Cytotoxicity was further enhanced with the use of the troxacitabine prodrug in combination with DZNep Prodrug 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, L-1,3-dixolane-cytidine (L-OddC) bearing a fatty acid group at its N 4 -position demonstrated significantly improved antitumor activity (170-fold) in vitro when compared to the parent nucleoside. 5 Fatty acyl derivatives of (−)-2′,3′-dideoxy-3′-thiacytidine (3TC) and (−)-2′,3′-dideoxy-5-fluoro-3′-thiacytidine [(−)-FTC] were 36- and 24-fold, respectively, more potent against HIV when compared to 3TC and (−)-FTC. 6 …”
Section: Introductionmentioning
confidence: 99%
“…In this way, one can consider these derivatives as prodrugs of 6a and 6b. Similar prodrugs against solid tumors have been synthesized recently [53]. From the activity data of 17a and 17b, it is not possible to conclude that the bromoacetamido group is a target for nucleophilic attack to yield carboxymethylated RT.…”
mentioning
confidence: 99%